CITRA DIGITAL DESA WISATA PENARUNGAN: MENELISIK PERAN MEDIA BARU DALAM PROMOSI PARIWISATA LOKAL - Widianti, Mira Adita; Pradhana, Yudha; Rahma, Alya (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2025)
This research discusses the utilization of new media in branding the Penarungan Tourism Village, located in Mengwi District, Badung Regency, Bali. The study was motivated by the increasing use of social media and websites as digital marketing communication tools, particularly in the tourism sector. The objective is to explore how village managers utilize new media to shape the image and attractiveness of the destination. This qualitative research collects data through field observations, social media documentation, and website analysis. The findings reveal that the use of Instagram, Twitter, and the official website has helped strengthen branding and increased the interest of both local and international tourists. New media significantly impacts audience interaction and promotional effectiveness. However, challenges such as content consistency, quality, and sustainable digital management remain.